In vitro and in vivo methods to assess pharmacokinetic drug– drug interactions in drug discovery and development. (7th January 2020) - Lu, Chuang; Di, Li
Abstract: Drug–drug interactions (DDIs) caused by the co‐administration of multiple drugs are major safety concerns in the clinic. Several drugs have been withdrawn from the market due to perpetrator or victim DDIs. Strategies have been developed to assess DDI risks early in drug discovery to reduce DDI liabilities. High‐to‐medium throughput assays are available to identify undesirable scaffolds and to guide structural modifications to minimize DDIs. Definitive methods are used at later stages of drug discovery and development to provide a more accurate measurement of DDI parameters and to enable clinical translations. Physiologically based pharmacokinetic modeling and simulations are powerful tools to accurately predict DDIs and to assess risks in the clinic. Although significant advances have been made over the years, many challenges remain for clinical DDI translations. This includes DDIs involving non‐cytochrome P450 enzymes, transporters, enzyme‐transporter interplay, indirect effects from biologics, and pharmacodynamic based DDI. This review focuses on methods that are used to assess hepatic DDIs caused by enzyme inhibition and induction.